Dissolved organic matter characteristics and nitrogen transformation rates in sediments of Pojo Bay, Finland - Sanni L Aalto; Eero Asmala; Tom Jilbert; Susanna Hietanen (PANGAEA, 2019)
Coastal environments are considered to be nitrogen (N) removal hot spots, regulating the amount of land-derived N reaching the open sea. However, gradual mixing of fresh and saline water masses alters the availability nitrate and bioavailable carbon from near-shore to offshore, which may alter the function of "coastal filter". Here, we combine stable isotope analysis, N2O measurements and organic carbon characterization, and show that a significant amount of the N removed in estuary is released as greenhouse gas nitrous oxide (N2O), while archipelago areas are characterized by efficient recycling of N in coastal Baltic Sea, challenging the current understanding on role of these regions as filters of land-to-sea transfer of N.